Psycho-diagnostic, a look at its history. - Yolanda Cabrera Macías; Ernesto José López González (Medisur)
Psycho-diagnostic is a branch of Psychology of great value for the diverse purposes of psychological, clinic, labor, educational and social evaluation. Antique texts show cites in which some men differ from others, but it is in 1978 with the emergence of the experimental Psychology, created by Wilhem Wund in Germany that a grater impulse is given to the use of the psychological tests. In 1921 the term psycho-diagnostic appears for the first time, in a monograph published by Hermann Rorschach, about the Stains test that has amply transcended to our days. It is included in this work, through a bibliographical revision, the most important tests for the development of Psychology in Cuba and the rest of the world; besides, the value of important personalities that have contributed to the development of methods and techniques of psychological evaluation is recognized.